Pulse combustion drying - Poh, Wei Bin. (2012)
Drying has been an essential process in the preservation of food, especially for grains such as rice, corn, soybeans, etc, which are usually exported to consumers worldwide. The growing global population coupled with rising energy costs results in soaring food prices which needs to be addressed quickly before it escalates to an astronomical figure. Many studies on pulse combustion carried out by researchers worldwide show great potential to be applied in the drying process to increase the output by reducing drying time required. The objective of this study is to investigate the drying rate of pulse combustion as compared to conventional continuous combustion drying. Soaked soybeans and green peas were dried in a custom-made drying chamber connected to a T-shaped Rijke tube, which acts as the pulse combustor, with and without pressure oscillation at the same fuel flow rate. The results indicated that at the fuel flow rate, the drying rate is reduced for pulse combustion due to energy loss in the form of sound energy with the onset of pressure oscillation in the Rijke tube. This study can be taken into consideration when conducting further studies to determine the efficiency of pulse combustion drying.